Dismantling doubt: a study on impostor phenomenon among women academics in South Africa - Ojetimi, Ribhat (Department of Sociology, 2025)
Impostor phenomenon is a psychological phenomenon manifested through feelings of self-doubt about intellectual competence, skills, and accomplishments despite evident success among individuals. This results in a constant fear of being exposed as a fraud, hindering their confidence and prospects for professional advancement. Transformation initiatives in South African higher education institutions aimed at increasing the representation of women and black people have seen a notable shift in the demographics of the profession. However, this shift has also coincided with rising levels of impostorism among these groups, highlighting the complex interplay between societal changes and individual experiences within academic spaces. Existing research has predominantly examined the impostor phenomenon from individualistic and psychological perspectives. However, a notable gap remains in understanding the sociological factors influencing the impostor phenomenon. The researcher argues that history, context, and culture are key in understanding the manifestation of impostorism among women and blacks in the academic profession of South Africa. This study contributes to this lacuna by conducting a sociological exploration of the impostor phenomenon among women academics at the University of Cape Town. In-depth qualitative interviews with women academics, underpinned by feminist intersectionality and socio-cultural and organisational cultural framing, illuminate the interplay of societal structures and organisational cultures in shaping experiences of impostor phenomenon. This not only provides a more complex and nuanced understanding of the phenomenon but also sheds light on the continued existence of inequality and marginalisation in the academic profession.